Efforts to Prevent Oil Spills in Accordance with Annex I Implementation on the MT Capella Ship - I Komang Gede Dimas Saputra; Sutoyo; Wulan Marlia Sandi; Upik Widyaningsih (International Journal of Science and Environment (IJSE), 2026)
Oil spills from tanker operations threaten marine ecosystems, especially in busy lanes such as the Malacca Strait, where operational failures in manifold connections during cargo handling are a major contributor to incidents. This study analyzes oil spill prevention efforts in accordance with MARPOL Annex I on the MT. Capella and identifies the causal factors through a descriptive qualitative case study. Data were collected from purposive sampling of key informants (Master, Chief Officer, Boatswain), semi-structured interviews, participant observation during 12 months of sailing practice, and analysis of ship documents, processed through thematic reduction, source triangulation, and interpretive verification. The findings indicate the systematic implementation of preventive measures including pre-operation toolbox meetings, visual inspections of reducers/gaskets/flange, installation of drip trays, and recording in the Oil Record Book, which successfully controlled a minor leak on February 17, 2025, without significant marine pollution. The main causes included technical factors (gasket wear, uneven bolt tightening, pressure surges) and human factors (lack of strict supervision, weak communication), confirmed through triangulation. The conclusions confirm that procedural compliance is effective but hampered by a lack of scheduled maintenance and scalable emergency response. Recommendations include standardizing torque wrenches, routine gasket stocking, intensive drilling, and regulatory audits to optimize Annex I compliance in Indonesian tanker operations.